2005
DOI: 10.2193/0022-541x(2005)069[1211:dwdapf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dusky-Footed Woodrat Demography and Prescribed Fire in a California Oak Woodland

Abstract: We investigated the effects of prescribed understory fire and shrub density on a population of dusky‐footed woodrats (Neotoma fuscipes) live‐trapped each spring and fall from October 1993 to 2001. We performed model selection with program MARK on capture‐recapture data using Pollock's robust design to estimate survival and temporary emigration. Abundance increased from 1993 to a peak in 1997 and then decreased steadily from 1997 to 2001, accompanied by reduced reproduction. Survival was age‐ and time‐dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…We expected that SOD-related mortality could act similarly to other forest disturbances such as logging or fire, which have been demonstrated to have important impacts on vertebrate populations (Bolger et al 1997; Lee and Tietje 2005; Suzan et al 2008a). We assessed whether SOD changed the abundances of key vertebrate hosts and the vectors of Lyme disease with potential consequences for Lyme disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…We expected that SOD-related mortality could act similarly to other forest disturbances such as logging or fire, which have been demonstrated to have important impacts on vertebrate populations (Bolger et al 1997; Lee and Tietje 2005; Suzan et al 2008a). We assessed whether SOD changed the abundances of key vertebrate hosts and the vectors of Lyme disease with potential consequences for Lyme disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a long-term study on small mammals (demography, relationships with habitat, and response to management of land; e.g., Lee and Tietje, 2005), we used mark-recapture data collected during 2002-2006 to quantify the short-term effects of repeated captures on woodrats in a relatively mild, two-season climate (cool wet winter versus hot dry summer) to provide a point of comparison with the results and implications of other studies. We also used the data to investigate long-term effects on survival of woodrats.…”
mentioning
confidence: 99%
“…Body mass is generally correlated with survival among small mammals (e.g., Myers and Master, 1983;Sauer and Slade, 1986), and younger, smaller individuals might be more susceptible to mortality due to starvation, exposure, predation, or other sources. Lee and Tietje (2005) determined that juvenile woodrats at Camp Roberts had lower survival than adults 1-2 years old. They further reported that survival of woodrats declines markedly after ca.…”
mentioning
confidence: 99%
“…The occupation of severely burned areas by small mammals is related to regrowth of the vegetation structure with which various species are associated (Torre and Díaz, 2004;Lee and Tietje, 2005;Vamstad and Rotenberry, 2010;Diffendorfer et al, 2012;Kelly et al, 2012;Borchert and Borchert, 2013), as well as with seed and insect production and availability (Coppeto et al, 2006), and cavities created by woodpeckers in snags (Tarbill, 2010). I discuss fire effects on small mammals according to habitat type but give special attention to the deer mouse (Peromyscus maniculatus)-an exceptionally "fire-loving" species-in its own section.…”
Section: Small Mammalsmentioning
confidence: 99%